Insertion/deletion (I/D) polymorphisms of angiotensin-converting enzyme gene and their implications for susceptibility and severity of COVID-19: A systematic review and meta-analysis - Fajar, Jonny K.; Tamara, Fredo; Putranto, Wachid; Prabowo, Nurhasan A.; Harapan, Harapan (Narra Sains Indonesia, 2024)
The insertion or deletion polymorphisms of the angiotensin-converting enzyme gene (ACE I/D) have been the subject of significant research related to coronavirus disease 2019 (COVID-19). Despite this, the findings have remained uncertain and debatable. The aim of this study was to determine the associations between the ACE I/D polymorphisms and the susceptibility as well as the severity of COVID-19. A meta-analysis study (PROSPERO: CRD42022384562) was conducted by searching the articles published on PubMed, Scopus, and Embase as of May 15, 2023. Information regarding the impact of ACE I/D variant on the susceptibility to COVID-19 and its severity was collected and analyzed utilizing the Mantel-Haenszel method with a random effects model or fixed effects model, depending on the presence or absence of heterogeneity. Out of 3,335 articles, 21 articles were included, of which 13 investigated the association between ACE I/D and the risk of COVID-19 infection and 18 of them examined its influence on disease severity. The D allele of ACE increased risk of COVID-19 infection (OR: 1.41; 95%CI: 1.08–1.85; p-Egger: 0.0676; p-Heterogeneity: <0.001; p=0.0120), while ACE I allele (OR: 0.71; 95%CI: 0.54–0.93; p-Egger: 0.0676; p-Heterogeneity: <0.001; p=0.012) and II genotype (OR: 0.55; 95%CI: 0.34–0.87; p-Egger: 0.200; p-Heterogeneity: <0.001; p=0.011) decreased the risk of infection. Additionally, there was a notable association between the ACE ID genotype and an elevated likelihood of experiencing severe COVID-19 within the Asian population (OR: 1.46; 95%CI: 1.15–1.84; p-Egger: 0.092; p-Heterogeneity: 0.116; p=0.002). The presence of ACE I/D polymorphisms significantly influences the likelihood of being susceptible to and experiencing the severity of COVID-19.